Determinasi Rasio Solvabilitas, Profitabilitas, dan Pasar pada Harga Saham LQ45 Sektor Perbankan - Adhistian, Patria; Handoyo, Agus F Handoyo; Ramadhani, Aulia Nazala; Nugraha, Nugraha; Wibowo, Priyo (Universitas Pamulang, 2024)
This research investigates the impact of solvency, profitability, and market ratios on stock prices within the banking sector listed on the LQ45 index in Indonesia from 2018 to 2022. The study aims to determine how Return on Assets (ROA), Debt Equity Ratio (DER), Earnings Per Share (EPS), Price Earnings Ratio (PER), Dividend Yield (DY), and Price to Book Value (PBV) influence share prices. Utilizing a quantitative approach, data were collected through library studies and analysed using Multiple Linear Regression with SPSS. The findings reveal that EPS, PER, and PBV have a significant positive effect on stock prices, while ROA, DER, and DY do not show a significant impact. This study highlights the importance of fundamental financial indicators in investment decision-making. Keywords: Fundamental analysis, LQ45, stock price, earnings per share, investment decision.